Above and below-ground growth, accumulated dry matter and nitrogen remobilization of wheat (Triticum aestivum) genotypes grown in PVC tubes under well- and deficit-watered conditions - Zhiipao, R. Rustum; Pooniya, Vijay; Kumar, Dinesh; Biswakarma, Niraj; Shivay, Yashbir Singh; Dass, Anchal; Kumar Bainsla, Naresh; Lakhena, Kamlesh K.; Pandey, Rakesh K.; Burman, Anamika; Bhatia, Arti; Jat, Ram D.; et al. (Frontiers in Plant Science, 2023)
The continuing decline in water resources under the ever-changing climate compels us to re-orient our focus to a more sustainable practice. This study investigates the performance of Triticum aestivum wheat genotypes viz. HD-2967, HD-3086, HD-3249, DBW-187, and HD-3226 under well- and deficit-watered conditions for their root-traits, biomass and nitrogen accumulation and remobilization, and water use efficiencies, grown in PVC-tubes. The genotypes HD-2967, HD-3086, HD-3249, DBW-187, and HD-3226 under well-watered (WW) resulted in 36, 35, 38, 33, and 42% more grain yield compared to deficit-watered (DW). Among the genotypes, HD-3249 had the highest grain yield under both well- and deficit-watered conditions. Compared to DW, the WW had 28%, 30%, and 28% greater root length, biomass, and root length density at flowering {102 days (d), Z61}, while among the genotypes, HD-3249 had relatively greater root-traits. At flowering (Z61) and maturity (132 d, Z89), genotypes under WW accumulated 30-46% and 30-53%, respectively greater shoot biomass over the DW. Furthermore, the shoot biomass remobilised for HD-2967, HD-3086, HD-3249, DBW-187, and HD-3226 under the WW was 32, 37, 39, 35, and 35% greater than the DW. The nitrogen partitioning to different plant parts at flowering (Z61) and maturity (Z89) was significantly greater with the WW than with DW. The total nitrogen-remobilized and contribution to grain-N under the WW was 55, 58, 52, 53, 58% and 9, 19, 15, 17, 17% greater than the DW for the genotypes HD-2967, HD-3086, HD-3249, DBW-187, and HD-3226. The irrigation water use efficiency (WUE) at flowering (Z61) was more under the deficit-watered, but the biomass and grain total WUE was improved with the well-watered condition. Hence, it is apparent that proper scheduling of irrigation and N applications, along with the adoption of a genotype suited to a particular environment, will result in better WUE and grain yields, along with better utilization of scarce resources.